TWO MATHEMATICAL MINDSETS AS A TECHNIQUE TO WRITE AN OBSERVATION RESULTS REPORT TEXT FOR STUDENTS AT GRADE IV - Refiana Putricipta Setiono; Triman Juniarso; Pana Pramulia (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Two mathematical mindsets are part of the four mathematical mindsets integrated into the technique of writing observation report texts, a writing method developed by Ayu Utami. This study aimed to investigate the effect of two mathematical mindsets on the students’ ability to write observation report texts in grade 4 at SDN Dukuh Menanggal 1 Surabaya. This research employed a quantitative approach with a quasi-experimental posttest-only design. The samples consisted of grade 4A students as the control group and grade 4B students as the experimental group. The t-test results showed that the t-count was 9.860, while the t-table was 2.0262 at a 5% significance level with 37 degrees of freedom. Since t-count (9.860) > t-table (2.0262), the hypothesis was accepted. The study concluded that the two mathematical mindsets technique significantly improved the students’ skills in writing observation report texts.